2011
DOI: 10.1080/10473289.2011.646050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seasonal phenol andp-cresol emissions from ground-level area sources in a dairy operation in central Texas

Abstract: Although there are more than 200 odor-causing volatile organic compounds (VOCs), phenol and p-cresol are two prominent odor-causing VOCs found downwind from concentrated animal feeding operations (CAFOs). The VOC emissions from cattle and dairy production are difficult to quantify accurately because of their low concentrations, spatial variability, and limitations of available instruments. To quantify VOCs, a protocol following U.S. Environmental Protection Agency (EPA) Method TO-14A has been established based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For the phenolic compounds (phenol, cresol and guaiacol), only emissions from biomass burning have been updated. Although emissions from other sectors, notably livestock (Borhan et al, 2012;Cai et al, 2011;Hobbs et al, 2004), have been reported in literature, no data suitable for a robust estimation of the emissions have been provided.…”
Section: Determination Of Marker Precursor Emissionsmentioning
confidence: 99%
“…For the phenolic compounds (phenol, cresol and guaiacol), only emissions from biomass burning have been updated. Although emissions from other sectors, notably livestock (Borhan et al, 2012;Cai et al, 2011;Hobbs et al, 2004), have been reported in literature, no data suitable for a robust estimation of the emissions have been provided.…”
Section: Determination Of Marker Precursor Emissionsmentioning
confidence: 99%
“…Similar to our observations, ammonia, sulfide, phenol, and p-cresol compounds have been commonly identified as one of the dominant odorants in a slurry and air sample of hog barn facilities. [6,29] In our recent study, the emission characteristics of major odorants in ambient air samples were measured from field sites such as each selected site from the same hog confinement facilities. When the results are compared in terms of OI, certain odorants (sulfur compounds, VFAs, phenols, and indoles) tend to occur most dominantly at most sites.…”
Section: Comparison Of the Treatment Efficiencies Over The Odor Compomentioning
confidence: 99%
“…It has been considered as a uremic toxin due to the correlation between serum p-cresol sulfate and endothelial damage in kidney disease [43]. In addition, p-cresol is widely considered as a prominent volatile organic compound responsible for the odor of concentrated cattle and dairy operations [44]. Therefore, decreased p-cresol in rumen fluid and decreased p-cresol sulfate in plasma and urine should be considered as beneficial effects of rutin consumption.…”
Section: Significance Of Inhibiting P-cresol Productionmentioning
confidence: 99%